Cultivating Mindfulness in Clinical Social Work : Narratives from Practice - Northcut, Terry B. (Essential Clinical Social Work Series, 2017)
This practice-focused resource integrates broad therapeutic knowledge with current neuroscience to present vast possibilities for mindfulness in clinical social work. Seasoned practitioners posit mindfulness practice and process as a significant bridge between taking care of self and taking care of others, demonstrating its implications for physical and mental health in personal and professional contexts. Case studies show timeless concepts (e.g., acceptance) and new mindfulness-based ideas (e.g., learned helpfulness) in use in individual treatment as well as couples counseling and group interventions. Also attesting to the utility of mindfulness across problems, settings, and practitioner orientations, diverse applications are organized along ten robust lenses, among them: - Beginning with the context: the mind-body conundrum. - Beginning with the body: the neurobiology of mindfulness. - Beginning with the training: training clinicians in essential methods for integrating mindfulness in clinical practice. - Beginning with the clients: mindfully reconciling opposites with survivors of trauma/complex traumatic stress disorders. - Beginning with the symptom: incorporating mindfulness in the treatment of substance misuse. - Beginning with the larger social system: mindfulness and restorative justice. Clinicians and research professionals particularly interested in psychotherapy treatment and mindfulness practice will find Cultivating Mindfulness in Clinical Social Work not only stimulating and intriguing, but also a fresh source of real-world wisdom.